Transparent diamond ceramics from diamond powder. Issue 3 (March 2023) - Zhang, Jiawei; Zhan, Guodong (David); He, Duanwei; Li, Dong; Li, Qian; Du, Congcong; Dai, Qiushi; Liu, Fangming; Yan, Xiaozhi
Abstract: Diamond possesses a unique combination of excellent optical, thermal, and mechanical properties, and is therefore an ideal transparent ceramic material for harsh and extreme environments. Due to its important applications in technology, transparent diamond ceramic (TDC) has been explored and prepared by chemical vapor deposition (CVD) or direct conversions of non-diamond carbon precursors at high pressure and high temperature (HPHT), but the preparation of large-size TDC with high mechanical strength remains a challenge. Here, we report for the first time, a transparent polycrystalline diamond ceramic from diamond powder with a transmittance of ∼60 % at wavelengths of 400–1600 nm. The analyses of phase composition, residual stress and microstructure evolution of the sintered samples with different sintering conditions indicate that compression at high temperatures (>2000 ⁰C) facilitates the deformation of diamond grains, allowing for densification and diamond-diamond bonding formation. The sintering pressure of the diamond powders with an optimized particle size distribution was dramatically reduced from 16 GPa to 10 GPa. Our results, based on successfully preparing centimeter-sized TDC, set the standard and the precedent for the large-scale preparation of larger TDC in proximity to industrial conditions.